Complications of Hypertension Patients with and Without Type 2 Diabetes Mellitus at the Poasia Public Health Center in Kendari City - Susanti, Risqi Wahyu; Baeda, Abd. Gani; Saputri, Ekawati; Tulak, Grace Tedy; Syahriyani, St. (Fakultas Kedokteran, 2024)
Background: The coexistence of hypertension and diabetes mellitus synergistically contributes to the risk of morbidity and mortality. Purpose: Determine the differences in complications between the group of hypertensive sufferers and the group of hypertensive sufferers with diabetes mellitus. Methods: This research is a quantitative study with an observational study approach conducted at the Puskemas Poasia Kendari City. The sample in this study was 90 people with 46 people in the hypertension group and 44 people in the hypertension group with diabetes mellitus. The sampling technique used is accidental sampling. Results: There were differences in complications between the hypertension patient group and the hypertension patient group with diabetes mellitus. Patients with hypertension 67.4% did not have complications while the group of hypertension with diabetes mellitus 59.1% had 1 complication with both microvascular and macrovascular complications. Conclusion: hypertensive patients with diabetes mellitus have more complications so appropriate interventions are needed to treat both diseases.Keywords: coexistence of hypertension, diabetes mellitus, hypertension